Economic Growth by Innovative Development in Energy Sector: The Case of Oil and Gas Export in Russia - Hoang, Hien Nguyen; Kashirin, A. I.; Strenalyuk, V. V.; Semenov, A. S.; Kazenkov, O. Y.; Chepurko, Yuri A. (International Journal of Energy Economics and Policy, 2022)
The problem of the "Dutch disease" and the impact of the raw materials complex and its export component on the economic development of Russia are actualized today in the context of the pressure of international economic sanctions on the Russian economy, when the Russian society has to solve problems that were characteristic of the Soviet Union, we mean, first of all, import substitution. In this regard, we need to understand how negatively the impact of energy exports on the socio-economic development of Russia was, while answering the question, was this development abnormal or, if so, due to what factors? Obviously, the crises in Russia in the 1990s and 2009–2011 had a nature weakly associated with raw material specialization. The purpose of this work is to identify the impact of energy exports on the economic development of Russia in retrospect with the construction of a long-term forecast of GDP growth in the Russian Federation in the context of the development of international economic sanctions. Accordingly, the objectives of the study include: to determine how economic growth in the post-Soviet period before the imposition of sanctions was affected by oil exports; secondly, to what extent oil exports influenced innovative development; thirdly, to create a predictive model for the growth of the Russian economy in the context of international sanctions (the situation with the embargo on Russian oil exports to the West). The subject of the study is the impact of oil exports on the socio-economic development of Russia, the object is the macroeconomic situation in Russia before and after international economic sanctions.